Improving Student Learning Activity in Islamic Jurisprudence Learning through the Application of the Contextual Teaching and Learning Model at Miftahul Ulum Mekarsari Elementary School - Warini; Widyalestari; Ningsih, Wetri; Herawati, Wati; Ibrahim, Warni (Jurnal Cendekia Islam Indonesia, 2025)
This study aims to improve students' learning activity in the Fiqh subject of zakat fitrah material through the application of the Contextual Teaching and Learning (CTL) model in class V of Madrasah Ibtidaiyah Miftahul Ulum Mekarsari. Students' learning activity is an important factor in the learning process that can affect the understanding of the material being taught. The CTL model was chosen because it can connect learning materials with everyday life, so that students can more easily understand and apply the material being taught. This study uses a qualitative approach with the classroom action method (CAR) which is carried out in two cycles. Data were collected through observation, interviews, and learning outcome tests. The results showed that the application of the CTL model can improve students' learning activity, both in terms of involvement in discussions, questions and answers, and zakat fitrah practice activities. In addition, students' understanding of zakat fitrah material also increased significantly. Thus, the CTL model is proven to be effective in improving students' activity and understanding in the Fiqh subject, especially zakat fitrah material in class V of Madrasah Ibtidaiyah Miftahul Ulum Mekarsari. It is hoped that the results of this study can provide a positive contribution to the development of learning methods in madrasah.